2002
DOI: 10.1111/j.1348-0421.2002.tb02705.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Tumor Mechanism of Z‐100, an Immunomodulatory Arabinomannan Extracted from Mycobacterium tuberculosis Strain Aoyama B, on Pulmonary Metastases of B16F10 Melanoma: Restoration of Helper T Cell Responses via Suppression of Glucocorticoid‐Genesis

Abstract: In the present study, the anti‐tumor mechanism of Z‐100 was investigated with the use of pulmonary metastasis of B16F10 melanoma. In B16F10 mice, Th1 cytokine production (IL‐2, IFN‐γ) was suppressed in comparison with normal mice. On the other hand, Th2 cytokine production (IL‐4, IL‐10) was increased in the B16F10 mice. The administration of Z‐100 to B16F10 mice restored the balance of Th1/Th2 cell responses from the Th2 dominant state to the normal state. Z‐100 significantly suppressed the pulmonary metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…10) On the other hand, it was reported that interleukin (IL)-12 and interferon (IFN)-g, induced by Z-100, lead to an improvement of type 1/2 T cell responses from type 2-dominated states to the normal states, resulting in suppression of tumor metastasis in mice bearing highly metastatic B16F10 melanoma cells (B16F10 melanoma). [11][12][13] Furthermore, Z-100 improved the balance of type 1/2 T cell responses in Meth-A tumor cell-bearing mice through both upregulation of IL-12 production from macrophages and IFN-g production from CD4…”
mentioning
confidence: 99%
“…10) On the other hand, it was reported that interleukin (IL)-12 and interferon (IFN)-g, induced by Z-100, lead to an improvement of type 1/2 T cell responses from type 2-dominated states to the normal states, resulting in suppression of tumor metastasis in mice bearing highly metastatic B16F10 melanoma cells (B16F10 melanoma). [11][12][13] Furthermore, Z-100 improved the balance of type 1/2 T cell responses in Meth-A tumor cell-bearing mice through both upregulation of IL-12 production from macrophages and IFN-g production from CD4…”
mentioning
confidence: 99%
“…23) Tumor MHC class I downregulation has been associated with tumor progression and metastasis. 24) Our present study, along with previous studies of Z-100 showing inhibition of hematogenous metastasis and primary tumor growth in B16 melanoma mice models, [15][16][17] suggest that Z-100 may inhibit cancer progression via a nonspecific increase in immune cells including CD4+ T, CD8+ T, NK and NKT cells. Z-100 may enhance immune responses in the lymph nodes than in other tissues in mice as the doses required to inhibit hematogenous metastasis and primary tumor growth (2, 10 mg/kg, respectively) are higher than that required to inhibit lymph node metastasis (0.1 mg/kg).…”
Section: Discussionmentioning
confidence: 88%
“…[15][16][17] In addition, a previous study reported that the induction of interleukin (IL)-12 and interferon (IFN)-γ by Z-100 led to a shift in CD4+ T cell activity from a type 2-dominant state to type 1-dominant, which was effective in inhibiting hematogenous metastasis in a mouse melanoma model. 15,17) However, it has not been confirmed whether Z-100 is effective on lymphatic metastasis and the contribution of CD8+ T cells, Natural Killer (NK) cells and Natural Killer T (NKT) cells by Z-100 is also unclear.The B16 melanoma lymphatic metastasis model is widely used to verify the effect of drugs on lymphatic metastasis. [18][19][20] In particular, the B16-BL6 melanoma subline was selected based on its invasive ability through the mouse bladder membrane, and transplantation into the footpad results in a high incidence of spontaneous metastases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These immunomodulatory properties have ultimately led to the use of such compounds in vaccination against mycobacterial infections and as immunotherapeutic agents in cancer therapy (11)(12)(13)(14)(15)(16)(17)(18)(19). AMs preparations show profound anti-tumor activity in murine experimental cancer models, and mechanistic studies reveal that the anti-tumor activity of AMs depends on distinct immune cell populations and TH1 cytokines (16,17).…”
mentioning
confidence: 99%